Perkembangan Motorik Halus Anak (Studi Empirisme dan Nativisme dalam Pendidikan) - Mahmudatunnisa, Ismi; Mawardi, Kholid (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Starting from the problem of fine motor development in children who experience disorders. This disorder can occur due to several things, for example autism, cesarean birth and so on. Children's development actually gets support from the surrounding environment and education. However, in reality there are two major currents in philosophy that conflict with the influence of education and the surrounding environment on this development, namely empiricism with the figure of John Locke and nativism with the figure of Arthur Schopenhauer. This paper uses a qualitative approach based on library research. To get a common thread between the two opposing schools, the author borrows Lewis Coser's term 'Rescue Valve'. As a result, both empiricism and nativism have an influence on children's education. On the one hand, children need learning experiences from the surrounding environment to hone their talents. On the other hand, nativism as a perspective can also be said to be correct because within a person there is always talent that has been acquired since birth. Thus, there are certain dimensions that can only be explained by empiricism or nativism. The two do not have to be in conflict, but can complement each other. This means that the problem of children's fine motor development can be overcome by understanding the child's basic nature while providing support from the surrounding environment.